Accidental intralenticular sustained-release dexamethasone (Ozurdex) implantation: A case report - Basu, Chaitali; Jha, Rakesh (Indian Journal of Case Reports, 2021)
Intravitreal implantation of Ozurdex (Allergan Inc., Irvine, CA, USA), a sustained-release dexamethasone implant, is a common practice in ophthalmology. Inadvertent intralenticular implantation of Ozurdex is a very rare complication. Herein, we report a case of accidental intralenticular Ozurdex implantation. During the intravitreal procedure, the patient moved his head vigorously which resulted in the said complication. He was followed up periodically with monitoring of intraocular pressure (IOP), best-corrected visual acuity, lens status, fundus, and macular edema status. He developed a posterior subcapsular cataract after about 5 months of the procedure. The cataract was removed around 6 months follow-up by phacoemulsification with anterior vitrectomy and implantation of a 3-piece posterior chamber intraocular lens in the ciliary sulcus. Macular edema had resolved by 3 months of Ozurdex implantation and the patient did not require a second intravitreal dose. He was well at 3 months follow up after cataract surgery.